2x3-3x2+3x-1 = 2x3 - x2 - 2x2 + x + 2x - 1
=(2x3 - x2) - (2x2 - x) + (2x - 1)
=x2(2x-1) - x(2x-1) + (2x - 1)
=(2x-1).(x2 - x - 1)
2x3-3x2+3x-1 = 2x3 - x2 - 2x2 + x + 2x - 1
=(2x3 - x2) - (2x2 - x) + (2x - 1)
=x2(2x-1) - x(2x-1) + (2x - 1)
=(2x-1).(x2 - x - 1)
Bài 1: Tìm x, biết:
a) 3x2-3x+2x3-2x2=0
b) x3+27=-x2+9
C3 .7x3-3x2-3x-1
C4 .2x3-5x2+x-2
a)A=3x(2/3x2-3x4)+(3x2)(x3-1)+(-2+9).x2-12
b)B=x(2x3+x+2)-2x2(x2+1)+x2-2x+1
c)C=x.(2x+1)-x2(x+2)+x3-x+3
tìm x
1. 3x - 7 = 19
2. (2x+1) . (x-3)=0
3. 3x+2/4 +1=5x-1/3
4. x/15 + 1/2 - x/50 = 5/6
5. x4 - 2x3 + 3x2 - 2x + 1=0
A= x. ( 2x + 1) x2 . ( x + 2 ) + ( x3- x+5 )
B= x . ( 3x2 - x + 5 ) - (2x3 + 3x - 16 ) - x . ( x2 - x + 2 )
Bài 1: Thực hiện phép tính
a)5x3(3x2 – 5x + 3) c)x2 ( 2x3 – 4x + 3)
b) -1\(\dfrac{1}{2}\)x22x – 1)(x2 + 5x – 4) d) (3x – 4)(2x + 4) + (5 – x)(2x2 + 3x – 2)
Phân tích các đa thức sau thành nhân tử:
a) 3x - 3y + x 2 - y 2 ; b) x 2 -4 x 2 y 2 + y 2 + 2xy
c) x 6 - x 4 + 2 x 3 + 2 x 2 ; d) x 3 - 3x 2 +3x - 1 - y 3 .
Tìm x
a) x2 + 3x - ( 2x+ 6) = 0
b) 5x+ 20- x2- 4x =0
c) 3x2- 3x+ 2x3-2x2= 0
d) x3+ 27= -x2+9
a)(-3x2+5x2-9x+15):(-3x+5)
b)(x4-2x3+2x-1):(x2-1)
c)(5x4+9x3-2x2-4x-8):(x-1)
d)(5x3+14x2+12x+8):(x+2)
Bài 2 ( 2đ): Tìm x, biết
a) x (x - 4 ) + 7 = 3x −5
b) 2x3 -3x2 - 2x + 3=0